2022
DOI: 10.1002/art.42153
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of Standard and Third‐Dose SARSCoV‐2 Vaccination in Patients Receiving Immunosuppressive Therapy

Abstract: Objective Immunogenicity and safety following receipt of the standard SARS–CoV‐2 vaccination regimen in patients with immune‐mediated inflammatory diseases (IMIDs) are poorly characterized, and data after receipt of the third vaccine dose are lacking. The aim of the study was to evaluate serologic responses and adverse events following the standard 2‐dose regimen and a third dose of SARS–CoV‐2 vaccine in IMID patients receiving immunosuppressive therapy. Methods Adult patients receiving immunosuppressive thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 45 publications
3
28
0
Order By: Relevance
“…The prospective, observational Norwegian study of vaccine response to COVID-19 vaccines (Nor-vaC) is an ongoing longitudinal observational study conducted at two Norwegian IMID centres; the Division of Rheumatology at Diakonhjemmet Hospital (DH) and the Department of Gastroenterology at Akershus University Hospital (AHUS). 7 Adult patients (aged ≥18 years) with RA, SpA, PsA, UC or CD who used any of the relevant immunosuppressive medications ( online supplemental appendix 1 ) were identified by the hospital records and consecutively recruited into the study prior to the initiation of the national vaccination programme in February 2021. Healthcare workers from DH, AHUS and Oslo University Hospital (OUH) were recruited as healthy controls ( online supplemental appendix 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The prospective, observational Norwegian study of vaccine response to COVID-19 vaccines (Nor-vaC) is an ongoing longitudinal observational study conducted at two Norwegian IMID centres; the Division of Rheumatology at Diakonhjemmet Hospital (DH) and the Department of Gastroenterology at Akershus University Hospital (AHUS). 7 Adult patients (aged ≥18 years) with RA, SpA, PsA, UC or CD who used any of the relevant immunosuppressive medications ( online supplemental appendix 1 ) were identified by the hospital records and consecutively recruited into the study prior to the initiation of the national vaccination programme in February 2021. Healthcare workers from DH, AHUS and Oslo University Hospital (OUH) were recruited as healthy controls ( online supplemental appendix 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that patients with IMIDs have an attenuated SARS-CoV-2 vaccine response compared to healthy controls at the first assessment after a standard two-dose regimen [ 12 , 15 ]. We now report continued low antibody levels in this 4-month follow-up study.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the impact of age on antibody decline, an agestratified multivariable regression was performed. [15][16][17][18][19][20][21][22][23][24] and 97 days [87-105] after second vaccine dose), and were included in the present study (Additional file 1: Fig. S3).…”
Section: Multivariable Linear Regressionmentioning
confidence: 99%
See 2 more Smart Citations